KEABSAHAN PRAKTEK PINJAMAN FINANCIAL TEKNOLOGI (FINTECH) DALAM MENJAMIN KEPASTIAN HUKUM TERHADAP KONSUMEN - Partogi Sihombing, Januardo Sulung (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Information technology-based money lending and borrowing services or commonly called peer to peer lending (P2P Lending) is a product from fintech that brings together fund owners (lenders) or what are usually called investors with fund borrowers or creditors (borrowers) or can also be called borrowers through electronic systems or information technology. From this, for the sake of legal certainty, there must be research regarding the legal certainty of fintech practices in Indonesia. The writing method used in this research is the Normative Juridical legal research method, namely research whose starting point is research on how the law applies in society and how the implementation of rules that already apply in reality in society, especially on the validity of financial technology (fintech) practices in guarantee legal certainty from the aspect of customer protection. The Law on Consumer Protection is an umbrella that integrates and strengthens law enforcement in the field of consumer protection and there is no possibility of the formation of a new law which basically contains provisions that protect consumers. With consumers. Therefore, consumers really need help with legal certainty regarding financial technology (fintech) practices in the aspect of customer protection. The condition of consumers who are weak and many have suffered losses requires increased efforts to protect them, so that consumer rights can be upheld. It should be noted that in providing protection to consumers, it must not actually kill business actors, because the existence of business actors is something essential in the country's economy.Keywords: Lending Practices, Fintetch, Legal Certainty, Consumers.